THE ROLE OF CRIME IN MODERATING THE IMPACT OF ECONOMIC GROWTH AND POVERTY: THE CASE OF WEST KALIMANTAN - Jamaliah, Jamaliah; Rusmita, Sari; Elyta, Elyta; Rosyadi, Rosyadi; Islahiyah, Djihan (Fakultas Ekonomi dan Bisnis, UNTAN, 2022)
This study aims to determine the effect of economic growth and education, which is thought to affect poverty. This study establishes crime as a moderating variable in fourteen districts and cities in West Kalimantan Province. The research data is panel data processed using a quantitative descriptive approach. We use a multiple regression model to seek the relationship between economic growth, education, and poverty, moderated by crime. The findings of this study illustrate that education affects poverty, while economic growth does not affect poverty. It has been discovered that crime plays an essential role in West Kalimantan to moderate economic growth into a better or worse condition of poverty. People's purchasing power and inequality in receiving benefits of growth tend to fail economic growth for reducing poverty. Also, crime has a strong relationship with education, and moderate education affects this Province's poverty. Government has to ensure a safe and conducive socio-economics condition to optimize the benefits of growth and education.JEL: I25, P25, R11.